2011
DOI: 10.1002/sia.3868
|View full text |Cite
|
Sign up to set email alerts
|

Study on structure of heat‐treated fullerene nanowhiskers and their field electron emission characteristics

Abstract: a Single-crystalline fullerene nanowhiskers heated in a high vacuum at 2373K were characterized by scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy. The field electron emission from the heat-treated nanowhiskers was studied by field emission microscopy. The outer shape of the heat-treated nanowhiskers maintained its original morphology before heat treatment, that is, a straight shape with a uniform diameter along the long axis and a hexagonal cross section, whereas the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The simulated C 60 fibers, the molecular stacking structures, and an hcp unit cell of the crystal are depicted in Figure d–f. Figure b shows the XRD traces of the freshly obtained C 60 fibers and those after treatment in vacuum at different temperatures for 4 h . It is observed that heating treatment makes the packing nature of fibers turned from hcp to fcc , gradually.…”
Section: Methodsmentioning
confidence: 99%
“…The simulated C 60 fibers, the molecular stacking structures, and an hcp unit cell of the crystal are depicted in Figure d–f. Figure b shows the XRD traces of the freshly obtained C 60 fibers and those after treatment in vacuum at different temperatures for 4 h . It is observed that heating treatment makes the packing nature of fibers turned from hcp to fcc , gradually.…”
Section: Methodsmentioning
confidence: 99%
“…Those C 60 NWs heated at high temperatures with developed graphitic ribbons are promising materials that may exhibit superconductivity if doped with alkali metals and alkaline-earth metals. In addition, the high-temperature-treated C 60 NWs become electron emission tips showing striped patterns that reflect the atomic structure of the crumpled graphitic layers [ 78 , 79 ]. However, since long amorphous carbon nanofibers prepared by high-temperature heat treatment of C 60 NWs showed cytotoxicity like long multiwall carbon nanotubes [ 96 ], special care will be necessary in the practical uses of the glassy carbon nanofibers.…”
Section: Electrical and Superconducting Properties Of C 60 mentioning
confidence: 99%
“…Reference source not found., the electrical properties of C 60 NWs vary from insulator to semiconductor depending on diameter. In addition, C 60 NWs become conductive glass-like carbon nanofibers following high-temperature heat treatment in an inert atmosphere [22]. Additionally, C 60 NWs can be made into superconductors by doping with alkali metals such as potassium [23] [24].…”
Section: Introductionmentioning
confidence: 99%